Studi Komparatif Hadis dan Tradisi Injil: Ajaran Etika dalam konteks antaragama : Keadilan, belas kasih, tanggung jawab - Ananda Aprilia Aulia Syahna; Hasan Su’aidi; Adi Abdullah Muslim; Taufik Abadi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article presents a comparative analysis of ethical teachings in the Hadith and the Biblical tradition (the Gospels), focusing on three universal values: justice, mercy, and social responsibility. This research is situated within the context of interfaith dialogue, aiming to foster interfaith understanding by emphasizing universal ethical values. This research examines the intersections and differences in the ethical systems of these two major religious traditions and their impact on social practices within religious communities, demonstrating that both traditions share universal values such as compassion, justice, and social responsibility. The research method used is library research across current academic sources, with a comparative analysis of normative texts. Data were obtained from primary sources (authentic Hadith and Gospel texts) and contemporary academic studies. The results show that despite differences in approach and application, both traditions emphasize fundamental values that promote justice and mercy in society. These findings highlight the potential of the ethical teachings of both religions to strengthen interfaith dialogue and promote social harmony. This research offers new insights through a comparative approach that focuses on normative texts, rather than merely comparing dogmatic theologies. This research concludes that both the Hadith and the Bible affirm a prophetic ethic grounded in the values of justice, compassion, and social responsibility. These findings offer new opportunities to develop interfaith public ethics as a foundation for dialogue and cooperation among religious communities in pluralistic societies.